COMPARATIVE SEMANTIC AND PRAGMATIC ANALYSIS OF TRANSLATION STRATEGIES IN JOHN GREEN’S "THE FAULT IN OUR STARS" (A RUSSIAN AND UZBEK CONFRONTATIVE STUDY) (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2026)
This article is devoted to a comparative analysis of the transfer of semantic and pragmatic features in the Russian and Uzbek translations of John Green’s novel The Fault in Our Stars. The study approaches translation as a process of intercultural communication in which the linguistic and cultural norms of the target audience determine the choice of translation strategy. The theoretical framework is based on Peter Newmark’s concepts of semantic and communicative translation, Christiane Nord’s Skopos theory, and Lawrence Venuti’s approaches to domestication and foreignization. Particular attention is paid to the translation of authorial metaphors, neologisms, performative speech acts, elements of adolescent discourse, and the existential themes embedded in the novel. The comparative analysis demonstrates that the Russian translation is primarily oriented toward preserving semantic equivalence and the author’s stylistic individuality, whereas the Uzbek translation employs a strategy of cultural adaptation through explication, mitigation, and the elimination of certain textual fragments. The findings indicate that such transformations ensure the text’s conformity with the socio-cultural and ethical norms of the target culture; however, in some cases, they weaken the philosophical depth, irony, and existential impact of the original. The results confirm that the choice of a translation macro-strategy is determined by the balance between preserving the author’s intention and accommodating the cultural expectations of the target readership.
Keywords: John Green, The Fault in Our Stars, literary translation, semantics, pragmatics, domestication, foreignization, intercultural communication, translation equivalence, existential discourse, Young Adult literature, translation transformations.